Construction of intelligent evolution network based on outbound call - Hua REN; Di YANG; Shaomin WANG (Dianxin kexue)
With the obvious improvement of various telecom business demands,the outbound call industry,which is the main channel for marketing,resolution and notification of telephone services under the traditional mode,is facing more and more pain points,including market,personnel,training,customer sentiment,cost,accurate data and people flow in all aspects.In order to realize the cost reduction and efficiency increase,inject wisdom and improve capability of telecom services,the main needs of the existing network outbound call system were combined with the application of artificial intelligence and big data technology in the field of outbound calls,aim to build intelligent and high efficiency.A discussion of the feasibility of the program was given based on the network construction involved in the efficiency of the ＆quot;smart outbound system＆quot;.